Insights into mechanisms of seed longevity in soybean: a review - Rao, Polneni Jagan Mohan; Pallavi, Mandalapu; Bharathi, Yarasi; Priya, P. Bindu; Sujatha, Patta; Prabhavathi, Kona (Frontiers in Plant Science, 2023)
Soybean, a crop of international importance, is challenged with the problem of seed longevity mainly due to its genetic composition and associated environmental cues. Soybean's fragile seed coat coupled with poor DNA integrity, ribosomal dysfunction, lipid peroxidation and poor antioxidant system constitute the rationale for fast deterioration. Variability among the genotypes for sensitivity to field weathering contributed to their differential seed longevity. Proportion and density of seed coat, glassy state of cells, calcium and lignin content, pore number, space between seed coat and cotyledon are some seed related traits that are strongly correlated to longevity. Further, efficient antioxidant system, surplus protective proteins, effective nucleotide and protein repair systems and free radical scavenging mechanisms also contributed to the storage potential of soybean seeds. Identification of molecular markers and QTLs associated with these mechanisms will pave way for enhanced selection efficiency for seed longevity in soybean breeding programs. This review reflects on the morphological, biochemical and molecular bases of seed longevity along with pointers on harvest, processing and storage strategies for extending vigour and viability in soybean.